2023
DOI: 10.1021/acs.analchem.3c00362
|View full text |Cite
|
Sign up to set email alerts
|

Chiral-Controlled Cyclic Chemiluminescence Reactions for the Analysis of Enantiomer Amino Acids

Abstract: The similarity and complexity of chiral amino acids (AAs) in complex samples remain a significant challenge in their analysis. In this work, the chiral metal–organic framework (MOF)-controlled cyclic chemiluminescence (CCL) reaction is developed and utilized in the analysis of enantiomer AAs. The chiral MOF of d-Co0.75Zn0.25-MOF-74 is designed and prepared by modifying the Co0.75Zn0.25-MOF-74 with d-tartaric acid. The developed chiral bimetallic MOF can not only offer the chiral recognize sites but also act as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Zhong et al modified CoZn bimetallic MOF-74 with d -tartaric acid to prepare a chiral catalyst. 185 The metal species as catalytic sites afford the luminol oxidation with the help of H 2 O 2 . The H-bond interaction between the d -tartaric acid and chiral amino acids enables control of the catalytic reaction rate for amplification of the signal difference.…”
Section: Applicationsmentioning
confidence: 99%
“…Zhong et al modified CoZn bimetallic MOF-74 with d -tartaric acid to prepare a chiral catalyst. 185 The metal species as catalytic sites afford the luminol oxidation with the help of H 2 O 2 . The H-bond interaction between the d -tartaric acid and chiral amino acids enables control of the catalytic reaction rate for amplification of the signal difference.…”
Section: Applicationsmentioning
confidence: 99%
“…We subsequently demonstrated that the decay coefficient of liquid-phase CCL relates to the rate constant . Recently, we synthesized a chiral metal–organic framework of D-Co 0.75 Zn 0.25 -MOF-74 that possesses double functions of a chiral host and sensitizer for the cyclic luminol–H 2 O 2 reaction, which was successfully used to differentiate 19 pairs of chiral amino acids …”
Section: Introductionmentioning
confidence: 99%